Ofícios e pequena indústria em Penafiel: Latoeiros/Funileiros - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
The Municipal Museum of Penafiel recently implemented an experience to stimulate the traditional crafts. It revealed that the tinsmith craft-deeply rooted in the city and district since the end of the 18th century-is at risk of vanishing, since only one professional craftsman remains, already retired. Such urgency led us to seek to document the activity, namely in the municipality, in order to construct a reading of this historical path, focusing on working dynamics and transmission of traditional skills, from the 18th century guilds to the Estado Novo (1933-1974). The last tinker and the memories of other craftsmen who learnt the trade in their youth and practiced it for many years, allowed access to working practices, technical means, models and needs and preferences of the clientele. These were considered under the relevant social and chronological context.